Factors associated with occupational roles in older Brazilians: a cross-sectional pilot study/Fatores associados com papéis ocupacionais em idosos brasileiros: um estudo piloto transversal - Rebellato, Carolina; Emmel, Maria Luisa Guillaumon; Cordeiro, Júnia Jorge Rjeille; Oishi, Jorge (Cadernos Brasileiros de Terapia Ocupacional, 2015)
Introduction: The Gerontology points out concerns in understanding aging and its consequences, in order to propose specific policies. Objective: Identify occupational roles of older Brazilians and the relationship of these roles to demographic, socioeconomic, and health factors. Method: Participants included 67 non-institutionalized individuals 70–84 years of age (33 men and 34 women; average age: 74.6 years). The roles performed in the Past, Present and Future were examined using the Role Checklist. Results: The occupational roles have changed over time, evidencing the loss of roles during the transition from Past to Present, although the participants stated that they intend to be engaged in a higher number of roles in the Future. The main roles performed in the Present are Hobbyist/Amateur, Home Maintainer and Family Member. In general, engaging in occupational roles was associated with higher education and income either in the Past, Present and Future. Conclusions: The study enabled to detect the diversity and complexity of older people’s participation in society, contributing to a further understanding of their occupational careers. The main limitation of this study concerns to the specific sample composition, with independent older people. Further studies are in need to obtain an in-depth theoretical and empirical understanding of the trends and trajectories of the roles of older people.